2015
DOI: 10.1002/star.201500272
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of plantain starch on a large laboratory scale

Abstract: Isolating starch from botanical sources has been widely reported on a small laboratory scale for characterization. However, isolation processes on a large laboratory scale intended for up-scaling have rarely been studied. In general, the laboratory-scale processes studied are batch processes, which limit the production rate for intensive commercialization. This work studied a large, laboratory-scale process for isolating starch from plantain fruits. The process is simple and involves a series of inclined sieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In contrast, starch extractions from non‐conventional sources yielded 55 g per 100 g with a purity of 89 g per 100 g for chayote tubers, [ 10 ] and of 37–49 g per 100 g with purity of 95 g per 100 g for plantains. [ 11 ] On the other hand, the amylose contents of oca starch in the present study were in the range reported by other authors for similar cultivars. [ 2–4,12 ] The DS of OSA‐modified oca starch was 0.014, a value that was similar to that of banana starches esterified with 3% OSA [ 13 ] and different to OSA‐oca pink obtained by Velásquez‐Barreto et al.…”
Section: Resultssupporting
confidence: 86%
“…In contrast, starch extractions from non‐conventional sources yielded 55 g per 100 g with a purity of 89 g per 100 g for chayote tubers, [ 10 ] and of 37–49 g per 100 g with purity of 95 g per 100 g for plantains. [ 11 ] On the other hand, the amylose contents of oca starch in the present study were in the range reported by other authors for similar cultivars. [ 2–4,12 ] The DS of OSA‐modified oca starch was 0.014, a value that was similar to that of banana starches esterified with 3% OSA [ 13 ] and different to OSA‐oca pink obtained by Velásquez‐Barreto et al.…”
Section: Resultssupporting
confidence: 86%